2007
DOI: 10.1166/jnn.2007.792
|View full text |Cite
|
Sign up to set email alerts
|

Micro Raman and Photoluminescence Spectroscopy of Nano-Porous n and p Type GaN/Sapphire(0001)

Abstract: Variation of depth within a single etching spot (3 mm circular diameter) was observed in nanoporous GaN epilayer obtained on photo-assisted electrochemical etching of n and p-type GaN. The different etching depth regions were studied using microRaman and PL(yellow region) for both n-type and p-type GaN. From Raman spectroscopy, we observed that increase in disorder is accompanied by stress relaxation, as depth of etching increases for n-type GaN epilayer. This is well corroborated with scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This result further indicated that the swelling behavior should be a common case in GaN-based materials under FIB irradiation. The reason why p-GaN is more likely to swell can be attributed to the fact that p-type GaN is more disordered than n-type GaN due to heavy Mg doping [24], and disintegration of Ga from the lattice is easier. Whether the swelling effect is emphasized or suppressed depends not only on the beam dwell time but also on the dopant type/concentration.…”
Section: Resultsmentioning
confidence: 99%
“…This result further indicated that the swelling behavior should be a common case in GaN-based materials under FIB irradiation. The reason why p-GaN is more likely to swell can be attributed to the fact that p-type GaN is more disordered than n-type GaN due to heavy Mg doping [24], and disintegration of Ga from the lattice is easier. Whether the swelling effect is emphasized or suppressed depends not only on the beam dwell time but also on the dopant type/concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In the photochemically-assisted environment, the location of the etching will give priority to the dislocation area, thus eliminating the dislocation and forming pores deep into the GaN at the current location. The phenomenon of phonon frequency reduction accompanied by peak displacement can be found in the generated NP-GaN under the Raman spectrum and calculated according to the stress relaxation formula [34]…”
Section: Feature Of Np-ganmentioning
confidence: 99%